PTH-044 A Single-centre Pilot Study Examining Internet Use For Health Related Information Among Patients With Inflammatory Bowel Disease. (9th June 2014) - Greveson, K; Shepherd, T; Hamilton, M; Murray, CD
Abstract : Introduction: The internet offers a wealth of information for patients with chronic disease, facilitating education and shared decision making; however, this can often be unregulated and inaccurate. 1 Inflammatory bowel disease (IBD) patients use of the internet has been investigated 2 but no studies have examined whether internet use alters with disease activity or influences patients decisions regarding health. We evaluated patients internet use for health-related information (HRI), including factors influencing website choice and whether this information influences decisions regarding healthcare or changes with disease severity. Methods: A prospective, pilot survey of 170 consecutive patients attending the IBD clinic over a one month period in November 2013. The anonymous questionnaire included demographic information on age, gender, education level, diagnosis and disease activity. There were also questions regarding use of the internet for HRI, determinants of website quality and influences of information found on the internet on decisions affecting their health. Results: A total of 136 IBD patients completed the questionnaire (80% response rate), 60 [44%] male, age 18–85 years [median age 37 years] 67 [49%] had CD; 84 [62%] reported a flare of symptoms in the preceding 6 months. 126 (93%) use the internet, 110 (81%) of which access HRI information via the internet. 94% of patients were educated to completion of high school or above and level of education did not affect internet use. Using NHS direct (46%), Crohn's and colitis UK (40%) and IBD forums (29%), patients searched for general health (77; 57%); IBD specific (63; 46%) and medication (47; 35%) information. 45 (33%) stated that information found on the internet would influence their choice of medication, irrespective of a flare within the last 6 months. 71% (96) felt confident that they could obtain factual information on the internet, although when determining website quality, overall appearance and position in search engines and whether the site was non-commercial were ranked least important and IBD-specific sites from a reputable source most important. Conclusion: In our study, internet use is shown to be a major source of disease –specific information and can affect patients' decision making. Internet usage and type of information sought do not alter with disease activity, suggesting that information is equally useful to all patients with IBD. References: 1 Fortinsky et al . Innflam Bow. Dis 2012; 18(6):1156–63 2 Cima et al . Inflamm Bowel Dis 2012; 13 (10)1266–1270 Disclosure of Interest: None Declared.